Tekanan, Kesempatan dan Rasionalisasi: Tiga Pemicu dalam Praktik Manajemen Laba - Wahyuni, Anggun Sri; Suci, Rama Gita; Ramashar, Wira (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
The purpose of this study is to examine how earnings management is affected by financial stability, external pressure, financial targets, ineffective monitoring, and rationalization. The research sample consisted of 24 State-Owned Enterprises listed on the Indonesia Stock Exchange between 2020 and 2023. Sampling was carried out using purposive sampling. There were 60 business samples throughout the period 2020–2023. The analysis tool used multiple linear regression tests. The results of this study indicate that financial stability has an effect on earnings management, external pressure has no effect on earnings management, financial targets have an effect on earnings management, ineffective monitoring has no effect on earnings management, and rationalization has an effect on earnings management. This study suggests expanding the research population to find out research results in various sectors and even countries.